Talking about forced pregnancy and sexual violence - Meléndez López, Liz Ivett (2016)
One of the worst manifestations of violence against women: sexual violation. The intent of this act is to humiliate, degrade and punish. This causes serious suffering inhumane treatment in women, affecting not only their physical but also mental health. Sexual violation can result not only an “unwanted” pregnancy but imposed through the exercise of power. The criminalization of abortion exposes survivors of violence to further suffering, ill-treatment and cruel situations by extension could be considered torture. This paper addresses these reflections, raising expand the legal dissertations on what is considered a “forced pregnancy” to include the pregnancy product of sexual violation in a context of prohibition of the right to decide, as such. For these reflections is part of the rights approach and gender, while also stating that reproductive rights of women not violence against women persist are guaranteed.